Neuroprotective therapy in acute ischemic stroke - A. A. Kulesh (Неврология, нейропсихиатрия, психосоматика)
The review discusses the role of neuroprotective therapy in the acute period of ischemic stroke in the era of active introduction of reperfusion treatment methods. The main mechanisms of brain damage during ischemia/reperfusion and the leading neuroprotective strategies studied in clinical trials are considered. Neuroprotective approaches aimed at suppressing excitotoxicity, oxidative stress, and neuroinflammation are presented. Current data on the safety and efficacy of uric acid, edaravone, fingolimod, natalizumab, interleukin 1 receptors antagonists, cerebrolysin, and other drugs have been analyzed. Non-drug methods of neuroprotection are characterized, including remote ischemic conditioning, therapeutic hypothermia, and neurostimulation. According to the author's position, the safest and most effective neuroprotective agent in acute ischemic stroke is cerebrolysin.